THE EFFECTIVENESS OF TEAM ASSISTED INDIVIDUALIZATION OF COOPERATIVE LEARNING ON MATHEMATICS LEARNING OUTCOMES - Devi Oktiani; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2019)
The direct learning method's use affects students' passive participation in classroom activities, resulting in poor mathematics learning outcomes. This study aims to know the effectiveness of team assisted individualization on mathematics learning outcomes of grade VII students of State Junior High School (SMPN) 1 Ngemplak, Sleman Regency in the even semester of the academic year 2017/2018. This study belongs to quantitative research. This study's populations were six classes of grade VII SMPN 1 Ngemplak, Sleman Regency in the even semester of the academic year of 2017/2018. Random sampling technique was applied to take the sample of this research: grade VII students class B in the treatment class; class E in the experiment class using team assisted individualization cooperative learning; and class C in the control class using direct learning model. The research instruments used in this study were multiple-choice tests. The research instruments were tested using a validity test, differential test, and reliability test. The data were analyzed using a normality test, homogeneity test, and hypothesis test for the prerequisite analysis, including t-test. From two-party t-test with of significance level and degrees of freedom resulted in . Thus is rejected. This means that students' mathematics learning outcomes between those taught using team assisted individualization cooperative learning and direct learning. A one-party t-test with a 5% significance level and degrees of freedom resulted in . Thus is rejected; it means that team assisted individualization cooperative learning is more effective than direct learning towards students' mathematics learning outcomes.